2016
DOI: 10.1021/acs.joc.6b01677
|View full text |Cite
|
Sign up to set email alerts
|

High π-Facial and exo-Selectivity for the Intramolecular Diels–Alder Cycloaddition of Dodeca-3,9,11-trien-5-one Precursors to 2-epi-Symbioimine and Related Compounds

Abstract: An unconstrained exocyclic stereogenic center and a removable trimethylsilyl group are combined to induce high π-facial selectivity and near-exclusive exo-selectivity in the intramolecular Diels-Alder cycloaddition of dodeca-3,9,11-trien-5-ones. This strategy provides direct access to polysubstituted trans-1-decalones related to the symbioimines in good yield and acceptable diastereoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Nevertheless, as was shown in this section and section , this mechanistic strategy can be a relatively mild and powerful tactic to both introduce amine functionality into a molecular framework and forge new C–C bonds in either an inter- or intramolecular fashion. The amino acid Dϕg and its various salts and esters are particularly attractive precursors to 2-azaallyl anion imine umpolungs as the resulting amine products are protected with the uniquely useful benzophenone imine functionality. , Future advances in this arena could come from both expanding the scope of intercepting electrophiles and identifying appropriate conditions to achieve the critical C–C bond-forming events with high levels of enantioselectivity.…”
Section: -Azaallyl Anionssupporting
confidence: 76%
See 1 more Smart Citation
“…Nevertheless, as was shown in this section and section , this mechanistic strategy can be a relatively mild and powerful tactic to both introduce amine functionality into a molecular framework and forge new C–C bonds in either an inter- or intramolecular fashion. The amino acid Dϕg and its various salts and esters are particularly attractive precursors to 2-azaallyl anion imine umpolungs as the resulting amine products are protected with the uniquely useful benzophenone imine functionality. , Future advances in this arena could come from both expanding the scope of intercepting electrophiles and identifying appropriate conditions to achieve the critical C–C bond-forming events with high levels of enantioselectivity.…”
Section: -Azaallyl Anionssupporting
confidence: 76%
“…The amino acid Dϕg and its various salts and esters are particularly attractive precursors to 2-azaallyl anion imine umpolungs as the resulting amine products are protected with the uniquely useful benzophenone imine functionality. 154,155 Future advances in this arena could come from both expanding the scope of intercepting electrophiles and identifying appropriate conditions to achieve the critical C−C bond-forming events with high levels of enantioselectivity.…”
Section: Reactions Of Semistabilized 2-azaallyl Anions Generated Via ...mentioning
confidence: 99%
“…To explore the utility of the Pd‐catalyzed DcPg reaction, silyl ether 18 first was subjected to 10 mol‐% Pd(PPh 3 ) 4 in THF at 65 °C, affording propargylated product 19 in 57 % isolated yield at gram scale (Scheme ). Partial hydrogenation of alkyne 19 in the presence of the benzophenone imine cleanly generated ( Z )‐homoallylic imine 20 (90 %). Other reported strategies for the synthesis of ( Z )‐homoallylic amines typically involve the addition of nucleophilic allylating agents into electrophilic imine components .…”
Section: Resultsmentioning
confidence: 99%
“…Symbioimine ( 1 ) possesses a tricyclic skeleton with an aromatic substituent, in which an iminium cation and a sulfonium anion form a zwitterionic pair. While several research groups have reported the synthesis of 1 , all syntheses employed an intramolecular Diels–Alder reaction of dienes possessing an aromatic substituent for the construction of the skeleton 4 10 , based on the proposed biosynthesis by Uemura 3 . However, this approach is not amenable to the syntheses of derivatives of 1 such as those with different aromatic groups for the improvement of the pharmacological activity, since the aromatic substituent was introduced at the early stage of the syntheses before the construction of the tricyclic core.…”
Section: Introductionmentioning
confidence: 99%